2011
DOI: 10.1007/s13580-011-0043-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aqueous chlorine dioxide and UV-C treatment on the microbial reduction and color of cherry tomatoes

Abstract: The effect of aqueous chlorine dioxide (ClO2) combined with UV-C irradiation on the postharvest quality of cherry tomatoes were examined. Cherry tomatoes were inoculated with Salmonella enterica serotype Typhimurium and Escherichia coli O157:H7, and then treated with 10 mg L -1 ClO2, 5 kJ m -2 UV-C, and a combination of ClO2/UV-C treatment. The populations of S. Typhimurium and E. coli O157:H7 in cherry tomatoes were reduced by 2.53 and 2.26 log CFU/g after treatment with aqueous ClO2, respectively. Treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 27 publications
1
10
1
Order By: Relevance
“…Electrolyzed water influenced positively the reduction of weight loss only in the first 10 days of storage, in fact, at the end of the storage period, the better treatment was chlorine dioxide, followed by Berry Very®, electrolyzed water and control, with losses of about 2.5%. Similar results have been reported with aqueous chlorine dioxide for blueberries and cherry tomatoes (Song et al, 2011).…”
Section: Discussionsupporting
confidence: 89%
“…Electrolyzed water influenced positively the reduction of weight loss only in the first 10 days of storage, in fact, at the end of the storage period, the better treatment was chlorine dioxide, followed by Berry Very®, electrolyzed water and control, with losses of about 2.5%. Similar results have been reported with aqueous chlorine dioxide for blueberries and cherry tomatoes (Song et al, 2011).…”
Section: Discussionsupporting
confidence: 89%
“…Postbloom fruit drop caused by Colletotrichum acutatum was reported in 2002 (35). Any foodborne outbreak damages the entire fresh produce industry for a long period of time (32); therefore, appropriate postharvest treatment is essential to prevent and control foodborne pathogens in fresh blueberries.…”
mentioning
confidence: 99%
“…Typhimurium with UV‐C treatment on flour powder. The levels of Salmonella spp., inoculated on Roma tomatoes were reduced 3.1 log CFU/g through UV‐C irradiation (500 mJ/cm 2 ) (Song, Choi, & Song, ). Compared to these previous studies, this study showed a weaker reduction effect.…”
Section: Resultsmentioning
confidence: 99%